Prevalence and Causes of Cognitive Impairment and Dementia in a Population-Based Cohort From Northern Portugal. Issue 1 (February 2019) - Ruano, Luis; Araújo, Natália; Branco, Mariana; Barreto, Rui; Moreira, Sandra; Pais, Ricardo; Cruz, Vítor Tedim; Lunet, Nuno; Barros, Henrique
Background: Vascular disease may play an important role in the epidemiology of dementia in countries with high stroke incidence, such as Portugal. Objective: To assess the prevalence and etiology of cognitive impairment in a population-based cohort from Portugal. Methods: Individuals ≥55 years (n = 730) from the EPIPorto cohort were assessed using the Mini-Mental State Examination and the Montreal Cognitive Assessment. Those scoring below the age-/education-adjusted cutoff points were further evaluated to identify dementia or mild cognitive impairment (MCI) and to define its most common causes. Results: Thirty-six cases of MCI/dementia were identified, corresponding to adjusted prevalences of 4.1% for MCI and 1.3% for dementia. The most common cause of MCI/dementia was vascular (52.8%), followed by Alzheimer's disease (36.1%). Conclusion: These findings highlight the importance of vascular cognitive impairment in the epidemiology of dementia in Portugal and carry an important public health message regarding its prevention and management, possibly extending to other countries with a high-stroke burden.